2022
DOI: 10.3390/d14090739
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptive Host Manipulation Hypothesis: Parasites Modify the Behaviour, Morphology, and Physiology of Amphibians

Abstract: Parasites have evolved different strategies to increase their transmission from one host to another. The Adaptive Host Manipulation hypothesis states that parasites induce modifications of host phenotypes that could maximise parasite fitness. There are numerous examples of parasite manipulation across a wide range of host and parasite taxa. However, the number of studies exploring the manipulative effects of parasites on amphibians is still scarce. Herein, we extensively review the current knowledge on phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Such manipulation by the pathogen to facilitate its transmission is well-known from many hostpathogen systems (Klein 2003;Hernandez-Caballero et al 2022). Besides other pathogens, viruses are also known to be able to modify the behaviour of their hosts to their advantage (Goulson 1997;Hanlon 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such manipulation by the pathogen to facilitate its transmission is well-known from many hostpathogen systems (Klein 2003;Hernandez-Caballero et al 2022). Besides other pathogens, viruses are also known to be able to modify the behaviour of their hosts to their advantage (Goulson 1997;Hanlon 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our study system, in the case of infected focal individuals, the observed increase in spatial proximity to the healthy conspecific might not necessarily result from avoidance of the infected stimulus but may be the manifestation of the pathogen manipulating the hosts’ behaviour: infection with Rv may have driven froglets to stay close to non-infected conspecifics. Such manipulation by the pathogen to facilitate its transmission is well-known from many host-pathogen systems (Klein 2003; Hernandez-Caballero et al 2022). Besides other pathogens, viruses are also known to be able to modify the behaviour of their hosts to their advantage (Goulson 1997; Hanlon 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Deformities in amphibians caused by trematodes were detected under the effects of several trematode species: Ribeiroia ondatrae (Price, 1931) in North America, Acanthostomum burminis (Bhalerao, 1926) Bhalerao, 1936 in Sri-Lanka, Holostephanus volgensis (Sudarikov, 1962) Vojtkova, 1966 and Strigea robusta in Europe and Asia [33,37]. The most investigated variant is the Ribeiroia ondatrae infection in the North American amphibians [4,13,27,50,[113][114][115][116][117][118][119][120][121][122][123].…”
Section: Role Of Planorbid Snails In Pathways Of Amphibian Parasites ...mentioning
confidence: 99%
“…[22][23][24][30][31][32]. In Europe, several hotspots are known in which trematodes change the morphology of second intermediate hosts [33]. One of these cases is the anomaly P syndrome hotspot found in some populations of water frogs and toads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation